WEWENANG PPK DALAM PENGADAAN BARANG JASA MENURUT PERPRES 12 TAHUN 2021 JO PERPRES 16 TAHUN 2018 TENTANG PENGADAAN BARANG JASA PEMERINTAH - Iskandar Ahmaddien (Lafadz Jaya Publisher, 2022)
Deviation from purchasing procedures One type of corruption is the provision of government services and goods that harm the economy or state finances. These deviations often occur because officials do not understand and comply with regulations or do not pay enough attention. This position is very important because the Commitment Making Officer (PPK) is involved in every stage of the government procurement process. As a result, PPK competencies must pay attention to morality and ethics, managerial competence, and the acquisition of goods and services. Parameters according to paragraph (1) of Article 2 and Article 3 of Law no. as amended by Law no. 31 of 2009 Acts of abuse of authority against the law are considered as a component of the crime of PPK based on Article 20 of the 2001 Corruption Crime Prevention Law. obligation. In the sense of applying statutory, conceptual, and statutory approaches to relevant cases, this research is normative in nature (normative law research). main problem at hand.